أثر التدخل الأجنبي في منطقة الساحل الإفريقي على الأمن الوطني الجزائري - بلحاج، سليم (جامعة باتنة 1 الحاج لخضر - كلية الحقوق والعلوم السياسية, 2024)
تعد منطقة الساحل الإفريقي أحد الفضاءات الأمنية البالغة الأهمية والتعقيد، لما تعرفه من تداخل وتشابك لتهديدات أمنية مختلفة، وتنافس بين القوى الكبرى، وانطلاقا من كون منطقة الساحل تشكل عمقا استراتيجيا ومجالا حيويا للأمن الوطني الجزائري، فإن الجزائر تتأثر بكل ما يحصل في هذا الفضاء سواء تعلق الأمر بتنامي التهديدات الأمنية المتأتية منه، أو بمختلف مشاريع القوى الكبرى، وفي ضوء ذلك سعت الدراسة إلى طرح فرضية أساسية وهي أن اشتداد التنافس بين القوى الكبرى على منطقة الساحل الإفريقي لفرض أجندتهم، يمثل تهديدا مباشرا للأمن الوطني الجزائري، ومن ثم خلصت الدراسة إلى أن التباين في المشاريع الأجنبية لمواجهة التحديات والتهديدات الأمنية في منطقة الساحل، باستنادها إلى مقاربات صلبة وارتباطها بصبغة تحقيق المصلحة، هو القاسم المشترك بين أدوار أغلب هذه الفواعل، وبالتالي تضييق هامش المناورة للجزائر في صون مصالحها الحيوية، ما يجعلها في كثير من الأحيان في موقف المواجهة غير المتكافئة مع هذه القوى. The African Sahel region is one of the most important and complex security spaces, due to the overlapping and intertwining of various security threats ancompetition between major powers. And based on the fact that the Sahel region constitutes a strategic depth and a vital area for Algerian national security, Algeria is affected by everything that happens in this space,d whether related to the matter is the growing security threats emanating from it, or the various projects of the major powers. In light of this, the study sought to put forward a basic hypothesis, which is that the intensification of competition between the major powers in the African Sahel region to impose their agenda represents a direct threat to Algerian national security, and then the study concluded that the discrepancy In foreign projects to confront security challenges and threats in the Sahel region, based on solid approaches and their connection to the nature of achieving interest, which is the common denominator between the roles of most of these actors, and thus narrowing the margin of maneuver for Algeria in preserving its vital interests, which often puts it in a position of asymmetric confrontation. With these powers.
Keywords: التدخلات الخارجية -- التهديدات الأمنية -- الأمن الوطني -- الجزائر